George Soros Speech for Hispanics in Philanthropy Conference (edited)
The edited version of George Soros’s address for the Hispanics in Philanthropy (HIP) conference. George Soros thanks HIP for the support given to the Emma Lazarus Fund and talks about the necessity to change the attitude towards immigration in the U.S.